BRAFV600E mutation as a predictor of thyroid malignancy in indeterminate nodules: A systematic review and meta-analysis. Issue 7 (July 2017) - Jinih, M.; Foley, N.; Osho, O.; Houlihan, L.; Toor, A.A.; Khan, J.Z.; Achakzai, A.A.; Redmond, H.P.
Abstract: Background: Thyroid nodules are usually diagnosed using fine-needle aspiration (FNA). The sensitivity limitations of FNA result in 10–30% of nodules being classified as "indeterminate". The BRAF V600E mutation is associated with papillary thyroid carcinoma (PTC). We conducted a systemic review and meta-analysis to evaluate the diagnostic utility of the BRAF V600E mutation in indeterminate nodules. Method: PUBMED and EMBASE were searched for studies testing for the BRAF V600E involving indeterminate nodules (Thy3a, Thy3f, Thy4) and containing information on final surgical histopathology. Thirty two studies involving 3150 indeterminate nodules were included in the analysis. Results: The overall sensitivity and specificity for BRAF V600E for the diagnosis of thyroid malignancy was 0.40 (95% CI: 0.32–0.48) and 1.00 (95% CI: 0.98–1.00) respectively. The diagnostic odds ratio (DOR) was 205.4 (95% CI: 40.1–1052). With a Fagan plot, the post-test probability of thyroid cancer, given a negative mutation was 6%, but this rose to 92% with a positive result. On subgroup analysis, for Thy3a nodules, the pooled sensitivity and specificity for thyroid malignancy was 0.21 (95% CI: 0.13–0.34) and 1.00 (95% CI: 0.98–1.00). For Thy3f nodules, the pooled sensitivity and specificity was 0.09 (95% CI: 0.03–0.20) and 1.00 (95% CI: 0.05–1.00) respectively. For Thy4 nodules, the corresponding sensitivity and specificity was 0.58 (95% CI: 0.5–0.64) and 0.99 (95% CI: 0.95–1.00) respectively. Conclusions: Despite a high specificity for thyroid cancer, BRAF V600E mutation has a low overall sensitivity and therefore has a limited diagnostic value as a single screening test.